Study on a 3D pounding pendulum TMD for mitigating bi-directional vibration of offshore wind turbines. (15th August 2021) - Jahangiri, V.; Sun, C.; Kong, F.
Highlights: An analytical model of an offshore wind turbine coupled with a three dimensional pounding pendulum damper (3d-PPTMD) has been established. The proposed 3d-PPTMD outperforms dual linear TMDs in mitigating bi-directional vibrations of offshore wind turbines. The stroke of the 3d-PPTMD is around 30 Under off-tuning effects, the 3d-PPTMD is more robust than dual linear TMDs and regular 3d-PTMD. Abstract: Misaligned wind and wave loading cause bi-directional vibrations of offshore wind turbines. In this study, a three dimensional pounding pendulum tuned mass damper (3d-PPTMD) is developed to reduce the vibration of a monopile type fixed-bottom offshore wind turbine in two directions. The proposed 3d-PPTMD is comprised of a pendulum mass-damper along with a cylindrical pounding layer where viscoelastic material is used to increase the dissipation of kinetic energy during pounding phase. A complete numerical model of the monopile fixed-bottom offshore wind turbine with the 3d-PPTMD is derived via Euler–Lagrangian equations. The wind loading is computed by the Blade Element Momentum approach, and the hydrodynamic loading is estimated via JONSWAP spectrum and Morisons equation. The effectiveness of the proposed 3d-PPTMD is examined on a monopile 5 MW baseline wind turbine subjected to misaligned wind and wave loading. The optimal design parameters of the proposed 3d-PPTMD are determined and its mitigation performance is examined under different loading scenarios and off-tuning effects. Dual linear TMDs and a regular three dimensional pendulum tuned mass damper (3d-PTMD) are employed for comparison. Results reveal that a well-designed 3d-PPTMD can effectively suppress the bi-directional vibration of the offshore wind turbine exposed to misaligned wind and wave loading. In addition, the 3d-PPTMD is more robust than the dual linear TMDs and regular 3d-PTMD to overcome the off-tuning effect. Moreover, the proposed 3d-PPTMD requires approximately 35 % and 25 % smaller space than the dual linear TMDs and the regular 3d-PTMD respectively, which is advantageous for real application.